Validity of a wearable device for measuring vertical displacement and jump count in young artistic roller skating athletes - Rebelo, A.; Teixeira, D. S.; Valente-dos-Santos, J.; Lima, R. F. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
The present study aimed to investigate the validity of a small inertial sensor (Vert IMU) for measuring vertical displacement and jump count in young female artistic roller skating athletes. Two separate investigations were completed. In the first, 12 subjects were asked to perform 24 jumps each, and jump heights were simultaneously assessed by the Optojump photocells (criterion instrument) and by the Vert IMU and compared to evaluate concurrent validity of this latter system. The second investigation evaluated the capacity of the Vert to correctly identify jumps during training sessions. The correlation between the Vert device and the Optojump was strong for all jump types (r = 0.84-0.95), except for the double Salchow which had a moderate correlation (r = 0.55). All 288 jumps in Investigation One had a significant (p < 0.001) mean bias of 9.96 cm with limits of agreement ranging from 1.58 to 18.34 cm. The results of Investigation Two indicate the Vert has excellent precision for all jump types analysed (0.968). In the elite group, recall was excellent for all jumps (0.900-1.000) besides the single Loop (0.364) and the single Thoren (0.444). However, in the sub-elite group, recall was excellent only in three jumps. The Vert device can offer a benefit in the sporting environment due to its capacity to provide near real time jumping data with limited resources. Some limitations regarding non-elite athletes may warrant some attention due to their lower vertical displacement ability and less-developed technical gestures in artistic jumping.